Nitrogen and phosphorus adsorption efficiency and mechanism of zeolite and biochar-based amendments in improving ecological substrate - Xinlong Zhou; Lin Gui; Henglin Xiao; Yunfeng Shi; Jiaqi Dou (Environmental Research Communications)
Non-point source pollution severely affected water bodies of river through riparian buffers. Ecological substrate is an efficient approach to reducing non-point source pollution. This study proposes an ecological substrate amended by zeolite and biochar for riverbank protection. The surface morphological characteristics and elemental distribution of the substrates were analyzed. The adsorption capacities of total nitrogen (TN) and total phosphorus (TP) under different substrate ratios were discussed. The results indicated that incorporating zeolite and biochar into the substrate significantly increases its specific surface area and pore volume, with BC-modified substrate (S-B) and composite-modified substrate (S-Z-B) showing a 273% and 45% enhancement, respectively, compared to the control group (S). The adsorption mechanisms for TN and TP on the amended substrates involve a synergistic effect of physical and chemical adsorption. Moreover, chemical interactions are the predominant controlling factors in the adsorption process of composite substrates. Comparably, the substrate amended by 6% zeolite and 1% biochar was identified as the optimal compositions for modified ecological revetment substrate.